1995
DOI: 10.1128/jcm.33.12.3209-3215.1995
|View full text |Cite
|
Sign up to set email alerts
|

Identification and antimicrobial resistance patterns of clinical isolates of Clostridium clostridioforme, Clostridium innocuum, and Clostridium ramosum compared with those of clinical isolates of Clostridium perfringens

Abstract: Clostridium ramosum, C. innocuum, and C. clostridioforme are frequently isolated from clinical specimens including blood. Because of Gram stain variability, a lack of spores, and atypical colonial morphology, identification of these species is often difficult. Three anaerobe identification kits were evaluated for their abilities to identify these species. For comparison, 11 strains of C. perfringens were evaluated in parallel. By using profile numbers and codebooks, the correct genus and species were identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
45
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(48 citation statements)
references
References 11 publications
3
45
0
Order By: Relevance
“…However, this conclusion is limited by the small number of patients in this cohort who did not receive an active antibiotic during the first 48 h after bacteraemia had developed (15%). Most studies assessing the antibiotic susceptibility of Clostridia have shown that most species, except C. tertium , are susceptible to penicillin, metronidazole, carbapenems and vancomycin . This large number of active antibiotics is probably the reason that the large majority of patient in this cohort were treated empirically with an active antibiotic within 48 h of bacteraemia.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…However, this conclusion is limited by the small number of patients in this cohort who did not receive an active antibiotic during the first 48 h after bacteraemia had developed (15%). Most studies assessing the antibiotic susceptibility of Clostridia have shown that most species, except C. tertium , are susceptible to penicillin, metronidazole, carbapenems and vancomycin . This large number of active antibiotics is probably the reason that the large majority of patient in this cohort were treated empirically with an active antibiotic within 48 h of bacteraemia.…”
Section: Discussionmentioning
confidence: 92%
“…Within 48 h of clostridial bacteraemia 45 of 164 patients (27%) were treated with a penicillin (penicillin G, mezlocillin, ampicillin or piperacillin) or clindamycin and 139 (85%) were treated with at least one antimicrobial agent with in vitro activity against most Clostridia including penicillins, clindamycin, metronidazole, vancomycin or carbapenems . Among the 25 patients who were not treated with an active antibiotic within 48 h, eight were treated with one or more antibiotics that are not typically active in vitro against Clostridia (ceftazidime, gentamicin, levofloxacin, ciprofloxacin) during the first 48 h, six were not treated with antibiotics (two of whom chose comfort‐focused medical care only), and the remainder started active antibiotics more than 48 h after bacteraemia had developed.…”
Section: Resultsmentioning
confidence: 99%
“…The present analysis of 16 incomplete genomes of Class Erysipelotrichi revealed that they have up to 10 genes of the 23 genes. Indeed, Pelosinus fermentans in Negativicutes and Clostridium ramosum in Erysipelotrichi form endospores (Alexander et al ., ; Shelobolina et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…Few previous studies have reported Clostridium species to be intermediately resistant or even strongly resistant to vancomycin (1,7,13). In two of these studies (7,13), varied clostridial species were tested as one group of uniform organisms, i.e., C. innocuum was not distinguished from the other species.…”
mentioning
confidence: 99%
“…Clostridium innocuum belongs to the normal intestinal flora of human infants and adults and is one of the species which have been reported to cause human infections, such as intra-abdominal sepsis, bacteremia, and endocarditis (5,9,12). However, its identification by commercial kits remains unsatisfactory and requires, therefore, the use of gasliquid chromatography and additional conventional tests (1). Clostridia are usually considered susceptible to vancomycin and teicoplanin (8).…”
mentioning
confidence: 99%